Cucurbitacin-B instigates intrinsic apoptosis and modulates Notch signaling in androgen-dependent prostate cancer LNCaP cells - Alafnan, Ahmed; Khalifa, Nasrin E.; Hussain, Talib; Osman, Mhdia Elhadi (Frontiers in Pharmacology, 2023)
Among numerous triterpenoids of the Cucurbitaceae family, Cucurbitacin-B is being explored for its pharmacological attributes. Reports from previous studies have explicitly shown that Cucurbitacin-B possesses substantial anticancer effects. The present report focuses on exploring the anticancer attributes of Cucurbitacin-B against androgen-dependent prostate cancer LNCaP cells. LNCaP cells were exposed to commercially available purified Cucurbitacin-B at varying concentrations that were selected as 5, 10, 15, 20, and 25 µM for some time of 24 h. Cytotoxicity evaluation revealed that Cucurbitacin-B impeded the LNCaP cell's viability at 5 µM (p<0.05) which increased considerably at a concentration of 25 µM (p<0.001). Cucurbitacin-B was also efficacious in inducing the changes within nu-clear morphology followed by a concomitant increase in the activities of key caspases including caspase-3, -8, and -9 intriguingly in a dose-dependent trend. Cucurbitacin-B treatment not only resulted in the augmentation of intracellular ROS levels within LNCaP cells at 5 µM (p<0.05) but also in-creased significantly at 25 µM concentration (p<0.001). Elevation in the ROS levels was also found to be correlated with dissipated mitochondrial membrane potential (ΔΨm) which culminated in the onset of significant apoptosis at 25 µM concentration (p<0.001).Cucurbitacin-B exposure also resulted in the downregulation of cyclin D1, cyclin-dependent kinase 4 (CDK4) followed by amplified levels of p21Cip1 mRNA. Importantly, exposure of Cucurbitacin-B competently reduced the expression of the Notch signaling cascade which may be the plausible cause behind Cucurbitacin-B-instigated apoptotic cell death and cell cycle arrest in LNCaP cells. These observations thus, explicitly indicated that Cucurbitacin-B could be plausibly further explored as potent therapeutics against androgen-dependent prostate cancer.